Graph Limits and Parameter Testing - Borgs, Christian; Chayes, Jennifer; Lovasz, Laszlo; Sos, Vera T.; Szegedy, Balazs; Vesztergombi, Katalin (2006)
We define a distance of two graphs that reflects the closeness of both local and global properties. We also define convergence of a sequence of graphs, and show that a graph sequence is convergent if and only if it is Cauchy in this distance. Every convergent graph sequence has a limit in the form of a symmetric measurable function in two variables. We use these notions of distance and graph limits to give a general theory for parameter testing. As examples, we provide short proofs of the testability of MaxCut and the recent result of Alon and Shapira about the testability of hereditary graph properties.